THE EFFECT OF STUDENT’S DIGITAL LITERACY AND SELF-EFFICACY ON STUDENTS LEARNING INDEPENDENCE WITH LEARNING MOTIVATION AS AN INTERVENING VARIABLE - Goutama, Eztro; Nurjanah, Siti; Pratama, Aditya (Transpublika Publisher, 2023)
This study aims to determine the effect of student digital literacy and self-efficacy on student learning independence in economic subjects through learning motivation as an intervening variable in South Jakarta State High School. This study is to determine the direct and indirect effects. Research using quantitative methods with data collection methods using questionnaires. The total population is 180 students from the sample used in class XI economics. The results of this research analysis are that there is a direct influence of student digital literacy variables on learning independence, there is a direct influence of self-efficacy variables on learning independence, there is a direct influence of learning motivation variables on learning independence, there is a direct influence of digital literacy variables on learning motivation, there is a direct influence of self-efficacy variables on learning motivation, there is an indirect influence of digital literacy variables on learning independence through learning motivation, good digital literacy can find information from various sources through the internet, so learning motivation will increase when it can get information easily which will have an impact on the independence of students in finding material and doing assignments independently. There is an indirect influence of self-efficacy variables on learning independence through learning motivation, Students who are able to increase their confidence in their ability to complete a particular task by having the desire and desire to succeed will encourage the emergence of learning independence in students.